Biallelic KIF24 Variants Are Responsible for a Spectrum of Skeletal Disorders Ranging From Lethal Skeletal Ciliopathy to Severe Acromesomelic Dysplasia. (19th July 2022) - Reilly, Madeline Louise; Ain, Noor ul; Muurinen, Mari; Tata, Alice; Huber, Céline; Simon, Marleen; Ishaq, Tayyaba; Shaw, Nick; Rusanen, Salla; Pekkinen, Minna; Högler, Wolfgang; Knapen, Maarten F. C. M.; et al.
ABSTRACT: Skeletal dysplasias comprise a large spectrum of mostly monogenic disorders affecting bone growth, patterning, and homeostasis, and ranging in severity from lethal to mild phenotypes. This study aimed to underpin the genetic cause of skeletal dysplasia in three unrelated families with variable skeletal manifestations. The six affected individuals from three families had severe short stature with extreme shortening of forelimbs, short long‐bones, and metatarsals, and brachydactyly (family 1); mild short stature, platyspondyly, and metaphyseal irregularities (family 2); or a prenatally lethal skeletal dysplasia with kidney features suggestive of a ciliopathy (family 3). Genetic studies by whole genome, whole exome, and ciliome panel sequencing identified in all affected individuals biallelic missense variants in KIF24, which encodes a kinesin family member controlling ciliogenesis. In families 1 and 3, with the more severe phenotype, the affected subjects harbored homozygous variants (c.1457A>G; p.(Ile486Val) and c.1565A>G; p.(Asn522Ser), respectively) in the motor domain which plays a crucial role in KIF24 function. In family 2, compound heterozygous variants (c.1697C>T; p.(Ser566Phe)/c.1811C>T; p.(Thr604Met)) were found C‐terminal to the motor domain, in agreement with a genotype–phenotype correlation. In vitro experiments performed on amnioblasts of one affected fetus from family 3 showed that primary cilia assembly was severely impaired, and that cytokinesis was also affected. In conclusion, our study describes novel forms of skeletal dysplasia associated with biallelic variants in KIF24 . To our knowledge this is the first report implicating KIF24 variants as the cause of a skeletal dysplasia, thereby extending the genetic heterogeneity and the phenotypic spectrum of rare bone disorders and underscoring the wide range of monogenetic skeletal ciliopathies. © 2022 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).